Certificateless Searchable Encryption With Trapdoor Unlinkability for Industrial Internet of Things - Sun, Lixue; Xu, Chunxiang; Zhang, Xiaojun; Zeng, Fugeng (IEEE systems journal, 2023)
Industrial Internet of Things (IIoT) is a promising application of Internet of Things (IoT) in the industrial sector, which greatly improves the manufacturing efficiency and enables the intelligent production. Nowadays, cloud computing has been introduced to handle the data management problem in IIoT. Nevertheless, how to retrieve ciphertext data remains a challenging problem. Recently, certificateless searchable encryption (CLSE) was proposed to tackle with this problem. CLSE allows the receiver to search the ciphertext data directly, meanwhile it protects the data privacy. However, existing CLSE schemes do not achieve the trapdoor unlinkability since deterministic algorithms are used to generate the trapdoors. Additionally, they cannot support multiple keywords search in one-time test operation. To address these issues, we propose a certificateless searchable encryption scheme with trapdoor unlinkability (CLSETU) for IIoT. We then demonstrate the semantic security of our scheme against insider keyword guessing attacks (KGA). Finally, the performance evaluation shows its feasibility in the deployment of IIoT.